Automated, Multistep Continuous‐Flow Synthesis of 2, 6‐Dideoxy and 3‐Amino‐2, 3, 6‐trideoxy Monosaccharide Building Blocks. Issue 43 (21st September 2021) - Yalamanchili, Subbarao; Nguyen, Tu‐Anh; Zsikla, Alexander; Stamper, Gavin; DeYong, Ashley E.; Florek, John; Vasquez, Olivea; Pohl, Nicola L. B.; Bennett, Clay S.
Abstract: An automated continuous flow system capable of producing protected deoxy‐sugar donors from commercial material is described. Four 2, 6‐dideoxy and two 3‐amino‐2, 3, 6‐trideoxy sugars with orthogonal protecting groups were synthesized in 11–32 % overall yields in 74–131.5 minutes of total reaction time. Several of the reactions were able to be concatenated into a continuous process, avoiding the need for chromatographic purification of intermediates. The modular nature of the experimental setup allowed for reaction streams to be split into different lines for the parallel synthesis of multiple donors. Further, the continuous flow processes were fully automated and described through the design of an open‐source Python‐controlled automation platform. Abstract : A continuous flow platform that is able to concatenate multiple steps for rapid, multi‐gram production of orthogonally protected deoxy‐sugars is described. Intermediate purification of compounds is avoided by the ability to run telescoped sequences of 2–4 chemical transformations. Through the use of Mechwolf, an open‐source, Python‐controlled program, automation of the flow processes was achieved.